Taburan Pb, Cr dan Cu di dalam bijih besi primer dan sekunder di Ladang Toh Pawang, Kedah : The distribution of Pb, Cr and Cu in the primary and secondary iron ore in Ladang Toh Pawang, Kedah - Habibah Hj. Jamil,; Wan Fuad Wan Hassan,; Mohammad Md. Tan, (Universiti Kebangsaan Malaysia, 2007)
There are two types of iron ore mineralization in Ladang Toh Pawang area, Kedah i.e. the primary and secondary ore. Very low concentrations of Pb and Cr are found in the primary ore (bdl) whereas Cu is found as impurity (60-93 μg/g). The concentrations of Cr and Cu increased at the contact between the intruding iron ore body and the country rocks. Their concentrations are 27-30 μg/g and 242-294 μg/g respectively. Enrichment of these metals is caused by the metasomatic replacement when the hot molten magma interacted with the ferrugeneous shales of Mahang Formation. Generally, the concentrations of Pb and Cr in the secondary iron ore are higher compared to the primary iron ore mineralization which ranges 3-7 μg/g and 121-151 μg/g respectively. The concentrations of Cu in primary and secondary iron ore are quite similar. Distribution of Pb, Cr and Cu in the secondary iron ore originated from the weathered ferrugeneouhttp://myjournal.ukm.my/cgi/users/home?screen=EPrint::Edit&eprintid=115&stage=core#ts shales of Mahang Formation. During surface processes, these metals were scavenged from ground waters and thus co-precipitated with the secondary iron ores.